Future Changes of Subseasonal Precipitation Variability in North America During Winter Under Global Warming. Issue 22 (20th November 2018) - Dong, Lu; Leung, L. Ruby; Song, Fengfei
Abstract: Changes in subseasonal precipitation variability have important implications for predictability of weather and climate extreme. Here we explore the mechanisms that lead to future changes in subseasonal precipitation variability in North America during winter based on 20 state‐of‐the‐art climate models. Modeling evidences indicate that in a warmer climate, the subseasonal precipitation variability consistently increases over most of North America, with intensified swing between the wet and dry extremes, but declines over Mexico. Using a moisture budget decomposition framework, two opposing mechanisms are established: the thermodynamic component from increasing moisture due to global warming intensifies the subseasonal precipitation variability, while the dynamic component from the projected reduction in subseasonal rainfall‐related circulation variability has an opposite effect. Overall, the thermodynamic effect wins the tug of war at the mid‐to‐high latitudes over most of North America, while the dynamic effect overwhelms the thermodynamic effect in Mexico, creating distinct changes in subseasonal precipitation variability. Plain Language Summary: There is an increasing demand for subseasonal forecast that bridges the gap between weather forecast and seasonal climate prediction. Although important progress has been made in subseasonal forecasting in the last decade, potential changes in subseasonal variability due to global warming may have important implications for subseasonal predictability. Here we found that subseasonal precipitation variability will increase over most of North America, with intensified wet and dry extremes under climate warming. However, subseasonal precipitation variability over Mexico will decline, with weakened extremes in the future. In response to warming, the effect of increasing background moisture is countered by the effect of weakening of subseasonal circulation variability, with the former dominating the enhanced subseasonal precipitation variability over the United States, while the latter dominates the weakened variability over Mexico. Changes in subseasonal precipitation variability and the swing between wet/dry extremes may have important societal and economic impacts. Key Points: Subseasonal precipitation variability will increase over most of North America but decline over Mexico from CMIP5 models under RCP8.5 Thermodynamic effect from increasing background moisture competes with dynamic effect from weakening of subseasonal circulation variability Thermodynamic effect dominates the enhanced variability over the United States, while dynamic effect dominates the weakening over Mexico